Use of Trauma-Informed Care With Incarcerated Offenders - Pringer, Sarah M. (Journal of addictions & offender counseling, 2020)
Regardless of preexisting trauma history, offenders regularly experience traumatic events while incarcerated. Current therapeutic approaches focus on coping skills and behavioral responses. The authors recommend integrating the use of trauma-informed care to address the deeper emotional responses tied to trauma.